Discovery of two active nests of Phytotoma raimondii, Tackzanowski, 1883, Peruvian Plantcutter - Rosina, Mario (2010)
Two nests belonging to Phytotoma raimondii, the Peruvian plantcutter, were found in El Gramadal, at Huarmey, Áncash. Both nests were in shrubs of Grabowskia boerhaaviaefolia, commonly known as palo negro. One nest had two eggs and the other nest had two chicks that were approximately two weeks old. Two weeks later, two fledglings were found following presumed parents. These chicks were close to the second nest, which was empty. These are the first nests reported for Phytotoma raimondii since 1934.